Physical properties of palm kernel olein-anhydrous milk fat mixtures transesterified using mycelium-bound lipase from Rhizomucor miehei - Liew, Margaret Y.B.; Ghazali, H.M.; Long, K.; Lai, O.M.; Yazid, A.M. (Elsevier, 2001)
The transesterification activity of mycelium-bound lipase from Rhizomucor miehei on palm kernel olein:anhydrous milk fat (PKO:AMF) blends was investigated. Commercial immobilised R. miehei lipase preparation, Lipozyme IM60 (Novo Nordisk), was used as a comparison. Mixtures of PKO:AMF, at ratios of 100:0, 70:30, 60:40, 50:50 and 0:100, were transesterified using either enzyme in a solvent-free system. The triglyceride (TG) profile, slip melting point, solid fat content, melting thermogram and the polymorphic form of the unreacted and transesterified mixtures were evaluated. Results indicated that transesterification by either enzyme was able to produce an oil mixture with new TG profiles, generally lower slip melting points and solid fat contents. The melting thermograms from differential scanning calorimetry analysis indicated changes in the triglyceride's crystalline composition and an overall shift to lower melting TG. Although the catalytic activities were similar for both lipases, Lipozyme-catalysed mixtures produced higher degrees of transesterification (43-51%) than mycelium-bound lipase-catalysed (22-34%) mixtures. This study also demonstrated that the transesterified PKO:AMF mixture at 70:30 ratio completely melted at 25C, and this meets the melting criteria for fat used in ice cream formulation.